Green financial policy and investment-financing maturity mismatch of enterprises - Zhang, Lingxiao; Zhang, Ke; Bilan, Yuriy (Journal of Business Economics and Management, 2024)
Green financial policies play an important role in acceleration of China’s green transformation. Existing associated studies mainly focus on the qualitative analysis and descriptive analysis. However, it still lacks empirical studies. To explore the relationship between green finance policies and the investment and financing terms of enterprises, the effects of green financial policies on investment-financing maturity mismatch of A-share companies on Shanghai Stock Exchange and Shenzhen Stock Exchange from 2009 to 2020 were investigated in this study by a difference-in-difference (DID) model. Results demonstrate that green financial policies significantly alleviate short-term loans used as long-term investment in enterprises. Green financial policies inhibit investment-financing maturity mismatch of enterprises by increasing loan availability, lowering financing cost and increasing proportion of long-term loans of enterprises. Such effect is more obvious in enterprises with higher internal control quality and enterprises with more transparent information. Green financial policies can alleviate short-term loans used as long-term investment in non-state-owned enterprises more obviously than state-owned enterprises. Research results provide some references to alleviate debt risks of enterprises. Enterprises are recommended to seek steady development, fulfil social responsibilities and take green low-carbon social actions extensively.